About the origin of the Lambe-Lambe Theater (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This article arises from a debate, a discussion, during the event “11º A Luz em Cena” [Held in September 2023, at the State University of Santa Catarina (UDESC) in Florianópolis], an event that encompasses the scenographic arts in its entirety, opening space for the discussion of various languages. The objective is to bring some references to address the origins of Teatro Lambe-Lambe and prevent them from running the risk of creating processes of invisibilization of Latin American women artists in relation to their creations. However, the aim is not to exhaust the references, but rather to indicate some so that they can access the information responsibly and avoid the spread of anything erroneous. It is an important article, to have a basis on what lambe-lambe theater is about, and then follow the discussions that have moved the lambeira community and that are also part of the scenographic arts.
Keywords: Lambe-Lambe Theater; women creators; origin; herstory